The impact of Brexit on International Students' Return Intentions - Jane Falkingham; Corrado Giulietti; Jackline Wahba; Chuhong Wang (Global Labor Organization (GLO), 2019)
This paper is the first attempt to study the causal impact of “Brexit”, namely the UK's departure from the European Union (EU), on the post-graduation mobility decisions of EU students in the UK. We exploit the British government's formal withdrawal notification under Article 50 as a natural experiment and employ a difference-in-differences design. Using data from a new survey of graduating international students, we find that EU graduating students are significantly more likely than non-EU graduating students to plan on leaving the UK upon graduation immediately after the announcement. Interestingly, results are especially driven by students from the new EU countries and students from the EU14 countries who are undecided of their migration plans. We further show that the deterrent effects are heterogeneous and depend on age and subject among others. These findings carry important implications for post-Brexit UK and for other European countries with emerging calls for their own referendums.
Keywords: 330; Brexit; Article 50; Higher education; International students; Intention to leave